Peran Hubungan Masyarakat Dalam Mewujudkan Transparansi Daerah - Jubaedah, Edah (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
This article describe the role of public relations in building local government transparancy. As transparancy concerned with the provision of appropriate, necessary, and relevant information to stakeholders when needed and upon demand; so the role of public relation in local government is ensure that the provision is fulfilled. Public relations in local government in doing so can adopt the concept of two-way symmetrical communication between local government is built based on the interest of stakeholders and the local government itself. In enhancing its roles, public relations in local government should enhance its organizational and individual capacity.